Comparative immature morphology of Brazilian fire ants (Hymenoptera: Formicidae: Solenopsis) - Fox, Eduardo Gonçalves Paterson; Solis, Daniel Russ [UNESP]; Rossi, Mnica Lanzoni; Delabie, Jacques Hubert Charles; De Souza, Rodrigo Fernando [UNESP]; Bueno, Odair Correa [UNESP] (Hindawi, 2012)
Although common in Brazil, the biology of the fire ant Solenopsis saevissima (Smith) is still poorly studied. Larval descriptions are useful to genus-level ant systematics and sometimes to species-level taxonomy. This study presents a detailed description of juveniles of S. saevissima from Brazil, which were compared with Brazilian specimens of Solenopsis invicta Buren, Solenopsis geminata (Fabricius), and Solenopsis altipunctata Pitts. Different larval instars were separated by diagnostic morphological traits which were confirmed by observing moults. Reproductive larvae could be easily sorted by their distinctive body dimensions and shape. Contrary to previous reports on this species, the larvae of S. saevissima proved to be generally identical to those of S. invicta, while a few specimens resembled those of other close species, such as Solenopsis megergates Trager. Mature larvae thus presented considerable intraspecific variation in some characters recently proposed to aid fire ant species separation (morphology of head hairs). © 2012 Eduardo Gonalves Paterson Fox et al.
Keywords: Formicidae; Hymenoptera; Solenopsis; Solenopsis geminata; Solenopsis invicta; Solenopsis megergates; Solenopsis saevissima